Deteksi Protein Bovine Major Histocompatibility Complex Klas I dan Klas II pada Sapi Madura - Suwiti, Ni Ketut; Abdul Rantam, Fedik; Kerta Besung, I Nengah (Jurnal Veteriner, 2008)
A study to detect the presence of bovine major histocompatibility complex (Bo-MHC) in maduracattle has been carried out. Lymphocyte samples were collected from 25 cattle. The protein of lymphocytesamples was analysed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) andtransferred onto nitrocellulose membrane. Bo-MHC proteins on the membrane were detected by monoclonalantibodies (anti-Bo-MHC class I) and BAQ150A (anti-Bo-MHC class II). The proteins of 48 kDa and 11kDa were detected by MAb B5C which appeared to be the alpha and beta chain of Bo-MHC class I. MAbBAQ150A detected protein band of 26 KDa which was likely to be the beta chain of Bo-MHC class II. Bo-MHC class I dan class II were clearly detected in madura cattle by MAbs which provides a basis for furtherinvestigation on the role of the MHC in the susceptibility the animals to many diseases.
Keywords: Bovine Major Histocompatibility Complex, madura cattle, monoclonal, antibodies